Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Find the values of [tex]\( p \)[/tex] and [tex]\( q \)[/tex] for which the expression

[tex]\[ x = 4x^4 - 6x^2 + px + q \][/tex]

is divisible by [tex]\( \left( x^2 - 1 \right) \)[/tex] without a remainder.


Sagot :

To find the values of [tex]\( p \)[/tex] and [tex]\( q \)[/tex] for which the expression [tex]\( x = 4x^4 - 6x^2 + px + q \)[/tex] is divisible by [tex]\( x^2 - 1 \)[/tex], we need to ensure that the expression does not leave any remainder when divided by [tex]\( x^2 - 1 \)[/tex].

The polynomial [tex]\( x^2 - 1 \)[/tex] can be factored as [tex]\( (x - 1)(x + 1) \)[/tex]. Therefore, for [tex]\( 4x^4 - 6x^2 + px + q \)[/tex] to be divisible by [tex]\( x^2 - 1 \)[/tex], it must yield zero when [tex]\( x = 1 \)[/tex] and [tex]\( x = -1 \)[/tex]. This gives us the following steps:

1. Substitute [tex]\( x = 1 \)[/tex] into the expression:
[tex]\[ 4(1)^4 - 6(1)^2 + p(1) + q = 0 \][/tex]
Simplifying this, we get:
[tex]\[ 4 - 6 + p + q = 0 \][/tex]
[tex]\[ p + q - 2 = 0 \][/tex]
This simplifies to our first equation:
[tex]\[ p + q = 2 \quad \text{(Equation 1)} \][/tex]

2. Substitute [tex]\( x = -1 \)[/tex] into the expression:
[tex]\[ 4(-1)^4 - 6(-1)^2 + p(-1) + q = 0 \][/tex]
Simplifying this, we get:
[tex]\[ 4 - 6 - p + q = 0 \][/tex]
[tex]\[ -p + q - 2 = 0 \][/tex]
This simplifies to our second equation:
[tex]\[ -p + q = 2 \quad \text{(Equation 2)} \][/tex]

3. Solve the system of simultaneous linear equations:
[tex]\[ \begin{cases} p + q = 2 \\ -p + q = 2 \end{cases} \][/tex]

- Add the two equations:
[tex]\[ (p + q) + (-p + q) = 2 + 2 \][/tex]
[tex]\[ q + q = 4 \][/tex]
[tex]\[ 2q = 4 \][/tex]
[tex]\[ q = 2 \][/tex]
- Substitute [tex]\( q = 2 \)[/tex] back into Equation 1:
[tex]\[ p + 2 = 2 \][/tex]
[tex]\[ p = 0 \][/tex]

Therefore, the values of [tex]\( p \)[/tex] and [tex]\( q \)[/tex] which make [tex]\( 4x^4 - 6x^2 + px + q \)[/tex] divisible by [tex]\( x^2 - 1 \)[/tex] without leaving a remainder are:
[tex]\[ p = 0 \quad \text{and} \quad q = 2 \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.